2022
DOI: 10.3389/ffgc.2022.836247
|View full text |Cite
|
Sign up to set email alerts
|

Mind the Gap: Reach and Mechanical Diversity of Searcher Shoots in Climbing Plants

Abstract: Climbing plants need to reach supports and position their leaves for light capture. Vines and lianas develop a large diversity of self-supporting shoots among diverse species and different kinds of attachment. A searcher’s reach is a crucial trait for colonising supports in complex three-dimensional spaces. We explore the reach capacity and diversity of searcher shoots among representative temperate and tropical climbing plants. We investigate the overall range of variation between short- and long-reach search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…This suggests a hard-wired, cutoff point where stiff juvenile wood development is stopped. It appears that the trellis-forming capacity across gaps can only be formed at a primary distance of c. 1.5 m represented by searcher maximal length—the approximate length of self-supporting searchers in this species ( Hattermann et al., 2022 ). There is no indeterminate or extended phase of support exploration as self-supporting stems.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This suggests a hard-wired, cutoff point where stiff juvenile wood development is stopped. It appears that the trellis-forming capacity across gaps can only be formed at a primary distance of c. 1.5 m represented by searcher maximal length—the approximate length of self-supporting searchers in this species ( Hattermann et al., 2022 ). There is no indeterminate or extended phase of support exploration as self-supporting stems.…”
Section: Discussionmentioning
confidence: 98%
“…Instead, there appears to be limit of three-dimensional (3D) space for which this species is adapted to exploit. In comparison with other searcher lengths ( Putz, 1984 ; Hattermann et al., 2022 ), different climbing plants have arguably undergone selection for specific habitats that include different distances between supports. In other words, at least for C. guianense , the plant does not invest materially in a self-supporting mode of growth for searching aerially further than that it was under selection for.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S7 ). Sled experiments were designed to apply a normal downwards force that approximated the ‘resting force’ for searcher shoots of each species at their maximum length or reach ( Hattermann et al , 2022 ). The results reported in this paper essentially represent the part of the stem that initiates initial contact to host supports and then twines around the host stem.…”
Section: Discussionmentioning
confidence: 99%
“…Photoreceptors and gravity-sensing cells are distributed throughout the apical shoot and are involved in phototropic (33,34) and gravitropic responses (35,36), respectively. To locate, reach, and interact with obstacles and potential supports, climbing plants produce an initial self-supporting stem whose stiffness and density decrease adaptively after location and attachment to an external support (37,38). It has been suggested that support localization by plants is driven by attraction to shade (39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%